Correlation Between Level of Depression and Risk of Suicide in Elderly at Purwodadi, Grobogan - Rilla Fiftina Hadi; Titis Hadiati; Natalia Dewi Wardani (Diponegoro International Medical Journal, 2020)
Background: According to WHO, the elderly people have physical and mental challenges, including depression. The incidence of depression lead to suicide on elderly is about 12.7%. In Grobogan Regency, Purwodadi, Central Java, there has been an increase of depression in the last 5 years. Purwodadi Subdistrict depends on the number of orders with the highest number of traffic cases and the elderly.Objective: To determine the correlation between depression level and the risk of suicide.Methods: This research is a quantitative study with cross sectional design in which all respondents were observed and variables were measured at one time. Samples were taken from elderly outpatient of primary health care and Posyandu lansia at Purwodadi, who met the inclusion and exclusion criterias. Research samples were selected based on nonprobability sampling method through purposive sampling. This research used the Indonesian version of the GDS (Geriatric Depression Scale) and CSSRS (Columbia Suicide Severity Rating Scale) questionnaire.Results: The prevalence of elderly depression is 63.3%, and a significant correlation was found between severe depression and low risk of suicide (p <0.05)Conclusion: significant correlation was found between severe depression and low risk of suicide.